The design and evaluation of targeted patient-centred health information to improve knowledge and behavioural outcomes in tuberculosis patients with limited literacy - Patel, Sonal (Rhodes University, Faculty of Pharmacy, Pharmacy, 2015)
South Africa carries a significant TB burden as evidenced in the 2013 statistics which report 450 000 new active TB cases and 890 000 TB-related mortalities. For successful treatment outcomes, 90% adherence is necessary, but many patients prematurely discontinue treatment due to poor knowledge and understanding of their complex TB medicines. Patient education is pivotal in improving knowledge, health literacy and behavioural outcomes such as health information seeking, self-efficacy and adherence. In the under-resourced South African healthcare system, time and capacity to adequately counsel patients are limited. The value of written medicine information (WMI) to supplement the verbal information provided by healthcare professionals (HCPs) has been widely investigated but minimal South African research is available. Current WMI distributed in South Africa is mainly generated by pharmaceutical manufacturers and is complex, incomprehensible and undesirable to patients. TB-related WMI focuses mainly on the disease, with little information relating to TB medicines and their use. The overall aim of this project was to improve patient knowledge about their TB medicines through the use of a simple illustrated patient information leaflet (PIL). Objectives to achieve this aim included: investigation of the medicine information seeking behaviour (MISB) of long term patients attending public health sector facilities; the development and validation of a medicine literacy test (MLT) to identify patients with limited health literacy requiring additional support and counselling; the development and evaluation of a patient-centred illustrated PIL for first-line TB treatment; the assessment of self-efficacy and adherence using modified versions of the HIV Treatment Adherence Self-Efficacy Scale (HIV-ASES) and Morisky 8-item Medicine Adherence Scale (MMAS-8), respectively, and the investigation of the impact of the PIL on patient knowledge and these health-related behaviours. Six focus group discussions (FGDs) conducted in 34 isiXhosa-speaking patients with limited formal education taking long-term treatment explored themes related to information needs, information-seeking practices and awareness of and ability to utilize information sources. Codes were analysed and potential themes and subthemes were identified and refined. The findings of this study reflected a passive, disempowered patient due to both patient-related and systemic healthcare factors. Poor awareness of information sources, lack of health-related knowledge, stigma and lack of awareness of the importance of appropriate medicine-related knowledge contributed to a lack of information-seeking practice. Patients neither asked questions nor were encouraged to do so. All expressed an unmet need for information and a desire for receiving relevant, appropriate, written medicine-related information. Feedback from this phase of the study was used to inform the development of the targeted patientcentred PIL. A double-sided A4 PIL containing information about TB medicines was designed giving careful consideration to content, format and layout features. Twenty five pictograms were designed through a rigorous, iterative design process and were included in the PIL that was evaluated in a randomised control trial (RCT) conducted amongst 120 TB patients attending a high burden TB clinic in South Africa. Interviews were conducted in either isiXhosa or Afrikaans via a trained interpreter. Patients were randomly allocated to either a control (standard care) or an experimental group (standard care plus brief counselling using the PIL). Two interviews were conducted using a prepared questionnaire; one at baseline followed by a 4-week follow-up. Baseline data included demographics, medicine literacy test, health information sources, knowledge of TB medicines, self-reported adherence and self-efficacy. Data collected at the 4-week follow-up interview included TB knowledge, self-reported adherence, self-efficacy, opinion of TB medicine information and interpretation of pictograms. Data were analysed using t-test, correlations, chi-square and ANOVA tests at a 0.05 level of significance. The PIL was successful in improving patient knowledge of the disease, TB medicine-taking, side effects, drug-resistant TB and HIV and TB co-infection. At baseline, there was no significant difference in the overall mean percentage knowledge score between the control and experimental groups (p=0.074). At follow-up, the percentage knowledge score for the experimental group increased significantly from 59.0% to 84.6% (p<0.001) and showed a significantly higher score than the control group (p<0.001), displaying evidence of the impact of the PIL as a counselling tool on patient knowledge. The PIL generated a highly positive response in the experimental group who indicated that they had referred to the leaflet over the last month and that it had played an important role in improving their TB medicine-related knowledge. This was reflected in the experimental group knowledge score of greater than 80% for almost three quarters of the patients whereas only 14% in the control group achieved this score. Patients appreciated the inclusion of pictograms and strongly felt that they helped them to recall and understand the textual PIL content. The study found that patients want side effect information and, interestingly, did not perceive the presentation of side effects in pictorial form to constitute a risk factor for nonadherence. Use of the illustrated PIL (experimental group) resulted in a significant improvement in patient self-efficacy (p=0.002), but showed no effect on self-reported adherence (p=0.563). Neither self-efficacy nor adherence was influenced by gender, age or education. An education effect on knowledge was only observed in the control group at baseline. The newly developed MLT was shown to be a valid and reliable tool and a moderate, positive and significant correlation was noted between the MLT score and baseline TB medicine-related knowledge in both the control and experimental groups. As there is a paucity of studies investigating the influence of take-home written leaflets on TB medicine knowledge and on patient behaviour, this study represents a significant knowledge contribution. It is the first study to report the development and evaluation of a patient-centred PIL to address the dearth of available TB medicine information. The use of targeted user-friendly, illustrated information leaflets can be a valuable counselling aid to improve patient knowledge and self-efficacy, particularly among patients with limited literacy. However, careful consideration of the design and content, with input from the endusers at all stages of the process, will optimise its effectiveness. The proposed framework for the development and implementation of patient-centred health and medicines information in a developing country context presented in this thesis could be used as a theoretical basis for informing the development of effective information materials targeting other disease states. Local patients taking TB medicines identified nurses, WMI and media as their current sources of information but they expressed a strong desire to know more about their treatment. Targeted public health interventions that focus on medicine-taking information and behaviours and encourage patients to adopt a more active, questioning role in health consultations could improve health literacy and empower patients in their medicine-taking practices.
Keywords: Tuberculosis Patients; Health literacy; Patient education; Communication in medicine; Picture-writing